Self-Critical Brand Communications: Conceptual Differentiation and Consumer Responses - Kale, Vaishnavi (IE University, 2025)
Brand communications have traditionally emphasized positive product attributes to foster favorable consumer perceptions. However, a growing trend in marketing deviates from this norm by embracing self-directed negative messaging. This dissertation introduces and investigates the novel phenomenon of Brand Communications with Self-Directed Negative Messages (BCSNMs), encompassing three distinct strategies: self-deprecation, humblebragging, and two-sided messaging. Despite their apparent counterintuitiveness, BCSNMs present significant opportunities for brands seeking to communicate effectively with consumers and build strong relationships. Chapter 1 establishes presents a comprehensive conceptual framework integrating psycholinguistic theories with the Elaboration Likelihood Model (ELM). It BCSNMs based on whether they are monosemic (single meaning) or polysemous (multiple meanings). Utilizing the ELM, this framework explains how varying consumer involvement influences their interpretations and responses to BCSNMs. This chapter clarities the interpretative processes underlying consumers’ evaluations and proposes an agenda for future research. Chapter 2 empirically tests consumer responses to self-deprecating advertisements and the brands who employ them through six experimental studies. Findings indicate that when self-deprecation targets less critical product attributes, consumers perceive brands as more socially attractive. This enhanced social attractiveness mitigates consumer skepticism, fosters brand trust, and reduces advertisement avoidance. In Chapter 3, the focus shifts to examining consumers’ product-related evaluations when exposed to self-deprecating advertisements. The chapter posits that self-deprecating messages, deliberately disclosing flaws, disrupt consumer expectations, prompting them to rationalize these weaknesses by inferring compensatory strengths in unobservable, experience-related attributes. Four experimental studies consistently confirm that self-deprecating (vs. self-promoting) advertisements prompt more positive, experience-focused consumer inferences. Overall, this dissertation contributes to marketing theory by systematically categorizing BCSNMs and empirically substantiating the nuanced strategic advantages of self-deprecation. It offers actionable managerial insights, emphasizing how marketers can effectively leverage transparent self-criticism to cultivate consumer trust, reduce skepticism, and positively shape product evaluations within increasingly skeptical consumer markets.
Comunicaciones de Marca Autocríticas: Diferenciación Conceptual y Respuestas del Consumidor
Las comunicaciones de marca han hecho hincapié tradicionalmente en los atributos positivos de los productos para fomentar una percepción favorable por parte de los consumidores. Sin embargo, una tendencia creciente en el marketing se aleja de esta norma y adopta mensajes negativos autodirigidos. Esta tesis doctoral presenta e investiga el novedoso fenómeno de las comunicaciones de marca con mensajes negativos autodirigidos (BCSNM, por sus siglas en inglés), que abarca tres estrategias distintas: el autodesprecio, la falsa modestia y los mensajes ambivalentes. A pesar de su aparente contradicción, las BCSNM ofrecen importantes oportunidades a las marcas que buscan comunicarse de forma eficaz con los consumidores y establecer relaciones sólidas. El capítulo 1 establece un marco conceptual integral que integra las teorías psicolingüísticas con el modelo de probabilidad de elaboración (ELM). Clasifica las BCSNM en función de si son monosémicas (un solo significado) o polisémicas (múltiples significados). Utilizando el ELM, este marco explica cómo la diferente implicación de los consumidores influye en sus interpretaciones y respuestas a las BCSNM. Este capítulo aclara los procesos interpretativos que subyacen a las evaluaciones de los consumidores y propone una agenda para futuras investigaciones. El capítulo 2 comprueba empíricamente las respuestas de los consumidores a los anuncios publicitarios autodespreciativos y a las marcas que los utilizan a través de seis estudios experimentales. Los resultados indican que, cuando el autodesprecio se centra en atributos menos críticos del producto, los consumidores perciben las marcas como más atractivas socialmente. Este mayor atractivo social mitiga el escepticismo de los consumidores, fomenta la confianza en la marca y reduce la evitación de los anuncios. En el capítulo 3, la atención se centra en examinar las evaluaciones de los consumidores relacionadas con los productos cuando se exponen a anuncios publicitarios autodespreciativos. El capítulo postula que los mensajes autodespreciativos, que revelan deliberadamente defectos, alteran las expectativas de los consumidores y los llevan a racionalizar estas debilidades infiriendo fortalezas compensatorias en atributos no observables y relacionados con la experiencia. Cuatro estudios experimentales confirman de manera consistente que los anuncios autodespreciativos (frente a los autopromociónales) provocan inferencias más positivas y centradas en la experiencia por parte de los consumidores. En general, esta tesis contribuye a la teoría del marketing al categorizar sistemáticamente los BCSNM y corroborar empíricamente las sutiles ventajas estratégicas del autodesprecio. Ofrece ideas prácticas para la gestión, haciendo hincapié en cómo los profesionales del marketing pueden aprovechar eficazmente la autocrítica transparente para cultivar la confianza de los consumidores, reducir el escepticismo y moldear positivamente las evaluaciones de los productos en unos mercados cada vez más escépticos.